Solving problems of non-equivalence when translating highly technical texts into an African Language : the translation of chemistry terms into isiZulu for a quadrilingual explanatory dictionary of chemistry (English Afrikaans isiZulu Sepedi) - Gauton, R. (University of Pretoria, 2016)
Mini Dissertation (MA)--University of Pretoria, 2015.